PERANCANGAN APLIKASI SURAT KETERANGAN TANDA LAPOR KEHILANGAN PADA KANTOR KEPOLISIAN RESOR SUMBAWA BERBASIS ANDROID - Esabella, Shinta (Jurnal TAMBORA, 2017)
The purpose of this writing is to identify the results of the analysis and the design of Application of Loss Signs Certificate (SKTLK) built by using Waterfall method, it is chosen because this method is a conventional and systematic model, sequential in building application software. The research begins with the stage of analyzing, designing, coding and testing. Although in the testing phase this application is merely able to run within the Localhost network, nevertheless it has provided the expected output as a basic concept for the presence of more complex and integrated application development, where the results of this study are expected to be one of the suggestions that contributes to the decision of the Highest Policy Holder on The Sumbawa Police Force to expand various applications within the Sumbawa Police Resort as one of the steps to improve the public service to the community.